(3fRgI GdSGeY aj GdYed HGdQHY GdLGeYs - (3Ydj Hf EHQGgje Hf eMeO GdCfUGQj GdehbJ, CHh GdMSf YdGA GdOjf, GdeYQha HGHf GdTGWQ,J (B777 (3g` s; (3GHf GdTGWQ , Ydj Hf EHQGgje Hf eMeO GdCfUGQj GdehbJ, YdGA GdOjf CHh GdMSf,J (B777 (3g` s
(3ChdgG (B:s
(3HYO GdOjGLg (B: (3agPg QSGdg GNJUQJgG ef GdQSGdg GdJi cfJ hVYJgG GdeSeGg HJMag GdSGeY aiGdYed HGdQHY GdLGeY s
(3BNQgG (B:s
(3hEf cGfJ eWGdYg CcKQ aGQJaGYg ZQHjG aGYde Pdc s
(3Vef eLehY , JQJjHgG (B: (3ef U (B22 - (3U(B34s
(3fSNI QGHYIs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B251 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B8s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B127 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B105 s
Keywords: (3Gdadcs